The application study of harmonization code in medical device adverse event reporting - Soo Jeong Choi; Sooin Choi; Songhyeon Park; Ki Chang Nam; Hye Jung Jang; Jin Kuk Kim; You Kyoung Lee; Hiroshi Ishikawa; Eric Woo (BMC Health Services Research)
Abstract Background The reporting of adverse events in medical devices (MD) is a starting point of post-market surveillance and the most common source of initial safety signals. Because MD adverse events (AE) occur globally and involve high-profile international public health crises, international regulators implanted standard codes for MDAE reporting. This study aimed to assess the application of MDAE terminology and codes by providing examples of virtual events. Methods An online survey was conducted among participants of the MD Training Program for Regulatory Authorities which provide International Medical Device Regulators Forum (IMDRF) adverse event terminology and codes, and six virtual MDAE cases. Results All 29 of the 72 participants were regulators. In all cases, most participants selected the broad (level 1) codes rather than the detailed (level 2 or level 3) codes. While responders selected a variety of codes for all annexes in case 1, over 50% of responders selected the intended codes in case 6. The codes for cause investigation were chosen more frequently than other annexes for device problem, components, and health effect. No differences were observed in code selection amongst different stakeholders. Conclusions We identified the diversification in terminology and code selection for reporting MDAEs.